2017
DOI: 10.1007/s11701-017-0715-z
|View full text |Cite
|
Sign up to set email alerts
|

Can teenage novel users perform as well as General Surgery residents upon initial exposure to a robotic surgical system simulator?

Abstract: New techniques in minimally invasive and robotic surgical platforms require staged curricula to insure proficiency. Scant literature exists as to how much simulation should play a role in training those who have skills in advanced surgical technology. The abilities of novel users may help discriminate if surgically experienced users should start at a higher simulation level or if the tasks are too rudimentary. The study's purpose is to explore the ability of General Surgery residents to gain proficiency on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…After self-training, both residents and staff physicians required less time to complete exercises and achieved improved scores; however, residents developed their robotic surgical skills more quickly. Previous studies have indicated that surgical experience, especially experience performing laparoscopic surgery, may not be advantageous in terms of the acquisition of robotic skills [25]. We con rmed that even residents with limited surgical experience could operate the surgical robot in the same manner as staff physicians during training and in actual clinical practice.…”
Section: Discussionmentioning
confidence: 60%
“…After self-training, both residents and staff physicians required less time to complete exercises and achieved improved scores; however, residents developed their robotic surgical skills more quickly. Previous studies have indicated that surgical experience, especially experience performing laparoscopic surgery, may not be advantageous in terms of the acquisition of robotic skills [25]. We con rmed that even residents with limited surgical experience could operate the surgical robot in the same manner as staff physicians during training and in actual clinical practice.…”
Section: Discussionmentioning
confidence: 60%